Chicken seller - Brand, Friedrich August, 1735-ca.1806 (engraver):::Creator::::::::::::; Brand, L., artist:::Contributor:::::::::::: (Austria; Mollo; Vienna)
Color engraving of a man selling chickens in Vienna